Towards sustainable electrochemistry: green synthesis and sintering aid modulations in the development of BaZr0.87Y0.1M0.03O3−δ (M = Mn, Co, and Fe) IT-SOFC electrolytes - Ain, Qurat ul; Irshad, Muneeb; Butt, Muhammad Salim; Tabish, Asif Nadeem; Hanif, Muhammad Bilal; Khalid, Muhammad Ali; Ghaffar, Rabia; Rafique, Muhammad; Shawar Kazmi, Syeda Dur E.; Siraj, Khurram; Hafez, Amal A. Abdel; Abd-Rabboh, Hisham S. M.; et al. (Frontiers in Chemistry, 2023)
In this study, BaZr0.87Y0.1M0.03O3−δ perovskite electrolytes with sintering aids (M=Mn, Co, and Fe) were synthesized by a sustainable approach using spinach powder as a chelating agent and then compared with chemically synthesized BaZr0.87Y0.1M0.03O3−δ (M = Mn, Co, and Fe) electrolytes for intermediate temperature SOFCs. This is the first example of such a sustainable synthesis of perovskite materials with sintering aids. Structural analysis revealed the presence of a cubic perovskite structure in BaZr0.87Y0.1M0.03O3−δ (M = Mn, Co, and Fe) samples synthesized by both green and conventional chemical methods. No significant secondary phases were observed in the samples synthesized by a sustainable approach. The observed phenomena of plane shift were because of the disparities between ionic radii of the dopants, impurities, and host materials. The surface morphology analysis revealed a denser microstructure for the electrolytes synthesized via green routes due to metallic impurities in the organic chelating agent. The absence of significant impurities was also observed by compositional analysis, while functional groups were identified through Fourier-transform infrared spectroscopy. Conductivity measurements showed that BaZr0.87Y0.1M0.03O3−δ (M = Mn, Co, and Fe) electrolytes synthesized by oxalic acid have higher conductivities compared to BaZr0.87Y0.1M0.03O3−δ (M = Mn, Co, and Fe) electrolytes synthesized by the green approach. The button cells employing BaZr0.87Y0.1Co0.03O3−δ electrolytes synthesized by the chemical and green routes achieved peak power densities 344 and 271 mW cm −2 respectively, suggesting that the novel green route can be applied to synthesize SOFC perovskite materials with minimal environmental impact and without significantly compromising cell performance.